Loneliness in older people with an intellectual disability - WORMALD, ANDREW DAVID (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2018)
Loneliness in Older People with an Intellectual Disability- Andrew David Wormald Abstract. Background: The causes, experiences and effects of loneliness in older people with an intellectual disability have never been investigated or modelled. Loneliness in ageing populations is often investigated using the Cognitive Discrepancy Approach to loneliness (Perlman & Peplau, 1998). Aims: This study created a model of loneliness in older people with an Intellectual Disability by investigating the antecedents, the characteristics and the consequences of loneliness. Methods: This study uses data from two waves of the Intellectual Disability Supplement to The Irish Longitudinal Study on Ageing (N=753), a nationally representative study of ageing in older people with an intellectual disability. Regression-based models formerly used to study loneliness in older people in the wider population were used. The findings of the models were combined to create a unified model of the CDA. Results The primary predisposing antecedent of loneliness was functional limitations. Transport difficulties, poor emotional health, reporting pain, service stress and wanting to do more activities all precipitated loneliness. Education to junior certificate level, working in the community and confiding in staff were protective against loneliness. Depressive attributions moderated the paths from antecedents to loneliness. Over 26% of participants were consistently lonely, 19% overcame loneliness, 12.5% became lonely, and 42% were never lonely. Consistent loneliness was predicted by; being older, being female, experiencing pain, falling, having difficulty doing activities and voting in the last election. Chronic conditions and holidaying abroad were protective against loneliness. Never being lonely was predicted by having a person-centred plan, being of high functional ability and not wanting to do more activities. Overcoming loneliness was predicted by changes in the frequency of visits from family and friends and becoming lonely was predicted by moving within the service provider organisation. Loneliness predicted raised systolic blood pressure (SBP) and sleeping difficulties. Confiding in staff was protective against loneliness. Consistent loneliness predicted having difficulty falling asleep, confiding in others, attending church regularly, reporting more life events and reporting an excellent or very good diet. People who did moderate exercise scored significantly higher on the loneliness scale. Structural equation modelling estimated a significant path from functional limitations through to raised SBP. Other paths were from experiencing transport problems to loneliness and from service stress to loneliness. Service changes and reliance on others for transport were specific to participants with more severe levels of ID. Discussion Twice as many older people with an ID remain consistently lonely compared to the general population. Functional limitations were the primary determinant of which variables precipitated unsatisfying relationships. Those with few functional limitations were more likely to live an independent life, and those with functional limitations lived a service dependent life. Relying on others for transport precipitated poor relationships in the independent group. Increased risk of pain changes in service provision and mental health problems precipitated unsatisfying relationships in the service dependent group. Negative attributions form the link from poor quality relationships to loneliness, in this population. Participants' uncontrolled responses were predictable, and their coping mechanism differed from the wider population. Lonely people experienced hypervigilance, which caused disturbed sleep, raised SBP, remembering more negative lifetime events and distrust of others. Loneliness was coped with by an encouraged strategy of active ageing. Loneliness can be tackled through the individualisation of services, which will improve the lives of older people with an ID and offers the potential of cost savings to the service providers.
APPROVED
Keywords: Consequences; IDS-TILDA; Intellectual Disability Supplement to The Irish Longitudinal Study on Ageing; Structural Equation Modelling; older; isolation; Attribution Theory; ID; Lonely; Antecedents; Aging; Cognitive Discrapancy Approach; Disability; Intellectual Disability; Loneliness; Ageing